John Hornby (1880-1927) - Stewart, Hugh (ARCTIC, 1984)
. John Hornby was 23 years old when he came to Canada from England in 1904. From then until his death 22 years later, he pursued a lifestyle uncomplicated by long-range goals and plans. . Hornby went north to the Great Bear Lake region with Cosmo Melville on a trading expedition in 1908. Fascination for the country was immediate, intense, and so strong that except for occasional trips to Edmonton, England, and service in the First Great War, he was to spend the rest of his life in the Barren Ground and the adjacent "land of the little sticks". . Hornby's practice of living off the land with an absolute minimum of food staples and equipment was irrevocably confirmed over the next few years. . in 1926 with two inexperienced companions . Hornby's ability to survive with a rifle, a bare minimum of food, and some good luck was not sufficient. In distinctively Hornby style, the party dallied high up on the Thelon for no explicable reason in the late summer, and missed the caribou migration southward. Consequently, they wintered without adequate food, and in the spring of 1927, all three succumbed to starvation in their cabin midway down the Thelon. Most likely, had the manner of Hornby's passing and the final depletion of strength and energy not been so dramatically and poignantly chronicled in Edgar Christian's diary, Hornby would only be a minor footnote in the history of subarctic travel. Yet, today, his status must surely approach that of a folk hero. He has been the subject of a number of books and articles, dramatic productions, and radio programs, and countless pilgrimages have been made to the site of his last cabin. . John Hornby is a popular legend because his story sparks the imagination of wilderness travellers of the late twentieth century. With him they have a natural empathy and affinity.